2008
DOI: 10.1056/nejmoa0802311
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine or Methotrexate Maintenance for ANCA-Associated Vasculitis

Abstract: These results do not support the primary hypothesis that methotrexate is safer than azathioprine. The two agents appear to be similar alternatives for maintenance therapy in patients with Wegener's granulomatosis and microscopic polyangiitis after initial remission. (ClinicalTrials.gov number, NCT00349674.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
270
4
31

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 601 publications
(312 citation statements)
references
References 26 publications
7
270
4
31
Order By: Relevance
“…Oral cyclophosphamide or azathioprine was indicated as an immunosuppressive agent during remission maintenance in the JMAAV protocol, but the agents were employed at the discretion of the attending physician. As the CYCAZAREM, WEGENT (Wegener’s granulomatosis-entretien trial) [19], and IMPROVE (international mycophenolate protocol to reduce outbreaks of vasculitides randomized trial) trials [20] have indicated that azathioprine is the best adjunctive immunosuppressant during maintenance treatment, the use of this agent for MPA patients should be analyzed in future trials. In addition, a tapering protocol was not determined in the JMAAV trial, and therefore the total amounts of glucocorticoid administered were greater than those outlined in the European recommendations (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Oral cyclophosphamide or azathioprine was indicated as an immunosuppressive agent during remission maintenance in the JMAAV protocol, but the agents were employed at the discretion of the attending physician. As the CYCAZAREM, WEGENT (Wegener’s granulomatosis-entretien trial) [19], and IMPROVE (international mycophenolate protocol to reduce outbreaks of vasculitides randomized trial) trials [20] have indicated that azathioprine is the best adjunctive immunosuppressant during maintenance treatment, the use of this agent for MPA patients should be analyzed in future trials. In addition, a tapering protocol was not determined in the JMAAV trial, and therefore the total amounts of glucocorticoid administered were greater than those outlined in the European recommendations (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Bosch et al reported that azathioprine and daily prednisone can maintain remission in patients who test negative for ANCAs, whereas patients positive for PR3 ANCA should be closely monitored because of a higher probability of relapse (28). Methotrexate has been shown to be equivalent to azathioprine, but it should not be used in patients with renal impairment (45). How long to continue maintenance therapy is not known, but at least 1 year since remission is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…B. dem Protokoll der sog. WEGENTStudie [179]. Auch die remissionserhaltende Behandlung mit RTX nach Induktion mit CYC wurde gemäß Studienprotokoll nicht später als 4 Wochen nach der letzten CYC-Gabe begonnen [68].…”
Section: Remissionserhaltende Therapie Nach Induktion Mit Cyclophosphunclassified